ANALISIS SWOT DALAM MENENTUKAN PROSES REKRUTMEN DAN SELEKSI KARYAWAN DI JNE EXPRESS CABANG UTAMA KOTA SORONG - Syahputra, Aji Mas; Sofia, Susetyowati; Rahayu, Agilistya; Andjar, Febry Jein (Yayasan Nuraini Ibrahim Mandiri, 2024)
This research aims to determine effective recruitment and selection strategies to increase deliveries carried out by JNE Express Sorong City Main Branchthrough SWOT analysis. This research uses qualitative research. Secondary data was collected through observation. Apart from observation, the author also used interviews with HRD and the head of Marketing at JNE Express Main Branch, Sorong City. The data that has been collectedthen analyzed using the SWOT method. The results of the research show that the total IFAS Matrix is 3.29 and the EFAS Matrix is 3.24, with the position in quadrant III showing that the strategy used is the Turn Around (WO) strategy with several strategies, namely inviting a trainer from JNE center to conduct training or seminars to develop employees' knowledge andskills in their field and conduct a trial period for new outsourcing employees.